Microstructural Material Analysis of Superalloy Inconel 792-5A after High Temperature Exposition - Jonsta, Zdenek; Jonsta, Petr; Mazanec, Karel (Communications - Scientific letters of the University of Zilina, 2009)
Aerospace industry often uses nickel superalloys for blades of jet engine turbines. The reason is that this material can satisfy numerous extreme requirements, such e.g. strength even at very high temperatures, resistance to fatigue damage, resistance to fatigue effect of combustion gases, etc. Long-term service life and material reliability is directly linked to its microstructure, or with its stability at long-term exploitation. Presented article deals with analysis microstructural material characteristics of cast variants nickel superalloy of INCONEL 792-5A type. Several strengthening mechanisms are applied in this type of superalloy. Principal mechanism is precipitation strengthening by coherent precipitates of intermetallic phase Ni3Ti, or Ni3(Ti,Al).The analysis as such is based on evaluation of microstructural parameters by application of electron microscopy and chemical microanalysis.